2011
DOI: 10.1007/978-3-642-23644-0_12
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Traffic Snooping in Tor Using Decoys

Abstract: Abstract. Anonymous communication networks like Tor partially protect the confidentiality of their users' traffic by encrypting all intraoverlay communication. However, when the relayed traffic reaches the boundaries of the overlay network towards its actual destination, the original user traffic is inevitably exposed. At this point, unless end-toend encryption is used, sensitive user data can be snooped by a malicious or compromised exit node, or by any other rogue network entity on the path towards the actua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…In 2011, Chakravarty et al [3] attempted to detect exit relays sniffing Tor users' traffic by systematically transmitting decoy credentials over all active exit relays. Over a period of ten months, the authors uncovered ten relays engaging in traffic snooping.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2011, Chakravarty et al [3] attempted to detect exit relays sniffing Tor users' traffic by systematically transmitting decoy credentials over all active exit relays. Over a period of ten months, the authors uncovered ten relays engaging in traffic snooping.…”
Section: Related Workmentioning
confidence: 99%
“…Our work is the first to give a comprehensive overview of active attacks. We further publish our code under a free license 3 . By doing so, we enable and encourage continuous and crowd-sourced measurements rather than one-time scans.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Using Decoy Traffic: Chakravarty et al [68] used decoy traffic on anonymous networks to detect traffic interception. The proposed strategy is based on the idea of injecting traffic containing bait credentials for decoy services requiring user authentication.…”
Section: Tor Attacksmentioning
confidence: 99%
“…One of these services is VPN Gate, an open and free service analyzed by Nobori et al [23]. Sporadic evidence so far has shown that traffic manipulation and monitoring also happens in other types of network relays, including open HTTP proxies [36] and even anonymity networks [5,43]. The work by Tsirantonakis et al studied header manipulation performed by over 65,000 open HTTP Proxies [36]: 5% of the tested proxies were found to perform malicious or unwanted modification.…”
Section: Vpn-based Measurementsmentioning
confidence: 99%